2013
DOI: 10.1016/j.stem.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Human Epidermal Stem Cell Function Is Regulated by Circadian Oscillations

Abstract: Human skin copes with harmful environmental factors that are circadian in nature, yet how circadian rhythms modulate the function of human epidermal stem cells is mostly unknown. Here we show that in human epidermal stem cells and their differentiated counterparts, core clock genes peak in a successive and phased manner, establishing distinct temporal intervals during the 24 hr day period. Each of these successive clock waves is associated with a peak in the expression of subsets of transcripts that temporally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
123
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 42 publications
6
123
0
Order By: Relevance
“…Consistent with the possible importance of this regulation, clock protein misexpression and/or a lack of circadian control has been documented in multiple tumor types (Hwang-Verslues et al, 2013; Luo et al, 2012;Zhao et al, 2013) and immortalized cell lines (Yeom et al, 2010). In normal physiology, circadian cell division has been documented in adult hippocampal neurogenesis (BouchardCannon et al, 2013), in intestinal and skin epithelial cell division (Geyfman et al, 2012;Janich et al, 2013;Karpowicz et al, 2013), and in multiple immune cell populations (Fortier et al, 2011;Keller et al, 2009) -essentially anywhere that cell division occurs in adult animals.…”
Section: From Cell Cycle To Tissues: Circadian Control Of Tissue Homementioning
confidence: 81%
See 2 more Smart Citations
“…Consistent with the possible importance of this regulation, clock protein misexpression and/or a lack of circadian control has been documented in multiple tumor types (Hwang-Verslues et al, 2013; Luo et al, 2012;Zhao et al, 2013) and immortalized cell lines (Yeom et al, 2010). In normal physiology, circadian cell division has been documented in adult hippocampal neurogenesis (BouchardCannon et al, 2013), in intestinal and skin epithelial cell division (Geyfman et al, 2012;Janich et al, 2013;Karpowicz et al, 2013), and in multiple immune cell populations (Fortier et al, 2011;Keller et al, 2009) -essentially anywhere that cell division occurs in adult animals.…”
Section: From Cell Cycle To Tissues: Circadian Control Of Tissue Homementioning
confidence: 81%
“…Given the importance of juxtacrine signaling during development, this heterogeneity might be important for optimizing cell fate decisions or could simply permit a broad population of cells expressing different receptors to respond to different cues at different times. In a subsequent study (Janich et al, 2013), the authors demonstrated the second possibility in vitro by showing that cultured and clock-synchronized keratinocyte stem cells responded better to certain differentiation cues at some times of day than at others. Consistent with their hypothesis, cells expressed different proliferation and differentiation pathway genes at different times of day.…”
Section: From Tissue Homeostasis To Stem Cells: Circadian Control Of mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the phase of circadian rhythms seems to play a role in differentiation. In human epidermal stem cells the phase of circadian rhythms determines proliferation predisposition (Janich et al 2013 ). When differentiation is induced by TGFβ or calcium, the core clock gene phase determines whether the epidermal stem cells respond to these cues.…”
Section: Circadian Clock Gene Expression In Adult Stem Cellsmentioning
confidence: 99%
“…This mechanism is heavily conserved throughout evolution and allows organisms to adapt and to synchronize themselves to diurnal fl uctuations in their environment. Circadian rhythmicity can be seen in many different life forms, ranging from unicellular organisms, like cyanobacteria, to highly specialized and stem cell heterogeneity (Janich et al 2011 ), cell division (Matsuo et al 2003 ;Kowalska et al 2013 ;Feillet et al 2014 ;Nagoshi et al 2004 ;Yang et al 2009;Unsal-Kaçmaz et al 2005 ), damage induced regeneration (Janich et al 2013 ), immune progenitor cell migration and differentiation (Scheiermann et al 2013 ;Yu et al 2013 ) as reviewed by Steven Brown ( 2014 ).…”
Section: Introductionmentioning
confidence: 99%